2021
DOI: 10.1001/jamaophthalmol.2021.0640
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Adverse Events With Intravitreal Anti–Vascular Endothelial Growth Factor Drugs

Abstract: IMPORTANCE Systemic safety of intravitreal anti-vascular endothelial growth factor (anti-VEGF) is a matter of debate and regular updates are necessary.OBJECTIVE To evaluate systemic adverse events (SAEs) associated with intravitreal anti-VEGF drugs compared with non-anti-VEGF treatments in patients with ocular diseases.DATA SOURCES Electronic searches were conducted in MEDLINE, Embase, and Cochrane Central Register of Controlled Trials databases from inception to July 7, 2020.STUDY SELECTION Randomized clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 70 publications
1
20
0
1
Order By: Relevance
“…Considering low incidence of the systemic adverse event in real world practice, meta-analysis may offer more dependable information. A most recent meta-analysis from JAMA Ophthalmology revealed that administration of anti-VEGF agents increased the risk of non-ocular hemorrhage in AMD patients (OR = 1.46, 95% CI 1.01–2.10); as well as increased risk of death in patients with diabetic retinopathy (OR = 1.80, 95% CI 1.03–3.16) 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering low incidence of the systemic adverse event in real world practice, meta-analysis may offer more dependable information. A most recent meta-analysis from JAMA Ophthalmology revealed that administration of anti-VEGF agents increased the risk of non-ocular hemorrhage in AMD patients (OR = 1.46, 95% CI 1.01–2.10); as well as increased risk of death in patients with diabetic retinopathy (OR = 1.80, 95% CI 1.03–3.16) 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal dexamethasone and anti-VEGFs involve distinct molecules and mechanisms; therefore, their effects may differ in terms of the risk of SAEs. Some meta-analyses of RCTs have reported that intravitreal dexamethasone and anti-VEGFs exhibited comparable systemic safety outcomes compared with placebo therapy [22][23][24][25]. Moreover, comparative RCTs have demonstrated similar systemic safety profiles for both dexamethasone and anti-VEGFs [20,26].…”
Section: Introductionmentioning
confidence: 99%
“…Pathologic retinal neovascularization [1] is a potentially blinding consequence seen in many common diseases including diabetic retinopathy [2], retinopathy of prematurity [3], retinal vascular occlusive diseases [4], and neovascular age-related macular degeneration (AMD) [5][6][7] among others. Epithelial membrane protein 2 (EMP2) has been shown to reasonably modulate activity through neovascularization network in the retinal pigment epithelial cell line ARPE-19 [8,9] which is reported to be important factors in progress of DR. To date, several studies have applied this approach to compare transcriptomes in vascular proliferation process within various cell types in humans [10,11], mice [12].…”
Section: Introductionmentioning
confidence: 99%